2016
DOI: 10.1016/j.peptides.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Lipid derivatives activate GPR119 and trigger GLP-1 secretion in primary murine L-cells

Abstract: HighlightsGPR119, a putative fat sensor, is a potential target for metabolic disease.KO of GPR119 in murine L-cells reduced GLP-1 response to fat in vivo.Primary L-cells secreted GLP-1 in response to GPR119 agonists.GPR119 agonists increased L-cell cAMP, with greatest efficacy in the colon.Our data support the use of GPR119 agonists to raise GLP-1 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 27 publications
4
44
0
Order By: Relevance
“…Similar findings were made in studies involving oleoyldopamide in wt and GPR119‐KO mice . Furthermore, the importance of dietary fat as a trigger of GLP‐1 release through GPR119 was recently demonstrated by the use of wt and GPR119‐KO mice . GPR119‐KO mice appear to have normal islet morphology, body weight and fed/fasted glucose levels .…”
Section: Discussionsupporting
confidence: 77%
“…Similar findings were made in studies involving oleoyldopamide in wt and GPR119‐KO mice . Furthermore, the importance of dietary fat as a trigger of GLP‐1 release through GPR119 was recently demonstrated by the use of wt and GPR119‐KO mice . GPR119‐KO mice appear to have normal islet morphology, body weight and fed/fasted glucose levels .…”
Section: Discussionsupporting
confidence: 77%
“…OEA and PEA do not act at cannabinoid receptors, but instead activate peroxisome proliferator-activated receptors (PPARs) that regulate lipid metabolism. OEA attenuates body mass gains and stimulates breakdown of fat through PPAR-á (Fu et al, 2003), but its peripherally-based anorectic effects (Rodriguez de Fonseca et al, 2001) may be in part due to its ability to activate GPR119 and elicit glucagon-like peptide-1 (GLP-1) secretion (Lauffer et al, 2009; Moss et al, 2016), which itself has anorectic effects in the hindbrain (Hayes et al, 2008). Thus we predicted that OEA would function in a direction opposite to that of endocannabinoids with respect to fat regulation; instead, we found that OEA concentrations correlated negatively with adiposity, much like our 2-AG findings.…”
Section: Discussionmentioning
confidence: 99%
“…An example of regional distinction is that GLP‐1‐secreting cells in the distal jejunum and ileum co‐express PYY, whereas proximal GLP‐1‐secreting cells co‐express CCK, GIP, neurotensin, or secretin . Although, traditionally, these enteroendocrine cells were differentiated by the peptides they secrete, recent research suggests that there is heterogeneous co‐expression of different peptides in these cells, and that these patterns of co‐expression differ between regions of the gGI tract . This process may enable enteroendocrine cells to respond to specific local nutritional stimuli .…”
Section: Mechanisms For Metabolic Successmentioning
confidence: 99%
“…25 Although, traditionally, these enteroendocrine cells were differentiated by the peptides they secrete, recent research suggests that there is heterogeneous co-expression of different peptides in these cells, and that these patterns of co-expression differ between regions of the gGI tract. 26 This process may enable enteroendocrine cells to respond to specific local nutritional stimuli. 27 Bariatric surgeries change not only the GI anatomy, but also the rate at which nutrients enter the intestine.…”
Section: Rygb Vsgmentioning
confidence: 99%